Barriers to Competition in Product Market Regulation : New Insights on Emerging Market and Developing Economies - Dauda, Seidu; Drozd, Maciej (World Bank, Washington, DC, 2020)
Reforms to foster competition in product markets have been shown to improve productivity and support economic growth in advanced economies (AEs). However, relatively little is known about restrictions to competition in emerging market and developing economies (EMDEs). We fill this gap by comparing product market regulations across 33 AEs and 37 EMDEs using standardized indicators developed by the Organization for Economic Co-operation and Development and collected jointly with the World Bank Group. Product market regulations are found to be more restrictive and more variable in EMDEs than in AEs. Most variation among countries can be attributed to differences in sector policies. This analysis allows policy makers to identify areas for reform and prompts policy researchers to investigate the links between product market regulation and economic development in EMDEs.